A safety-based flight scheduler and management system. - Atan, Rodziah (2009)

(untitled)
The present invention relates to a safety-based flight scheduler and management system. The system is a hardware-embedded system to support scheduling, estimation and dynamic environmental safety caution alerting for flight trips from one destination to another. An intelligent agent that is capable to produce decision options for unusual situation (dynamic environment such as sudden weather changes)will be applied to the application to coupe with real-time safety precautions. Preferably, the system is a plug-and-play scheduler and management system which does not require installation and minimizes utilization of central processing units space.